Retaining and maintaining High-Level Client Relationships in South African Commercial Property finance - Reddy, Quewin (My University, 2012)
In recent years, commercial property finance divisions within the five big South African banks have experienced reduced growth and increased risks within the environments in which they operate. The global economic slowdown and market trends have forced the commercial property finance divisions to focus more attention on the retention and maintenance of their current clients by fulfilling their needs quickly and accurately. The objective of this research was to determine the critical success factors in the retention and maintenance of high level client relationships within the commercial property finance environments in South Africa. The methodology used was qualitative, semi-structured interviews. The sample was drawn from each of the five banks business banking divisions and from their customer bases. Two business banking staff from each of the banks and five customers were interviewed. The main findings of the research were that customer retention and maintenance was dependant on:  Customer loyalty;  Customer relationship management;  Customer retention management;  Customer satisfaction;  And Leadership. All of the above five areas were found to have a direct impact on client retention and maintenance in the commercial property finance divisions with South Africa.
MBA thesis (WBS)
Keywords: Client relationships; Property industry; Commercial property